Method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud and application of water purification filter material

By collaborating the use of waste incineration fly ash and red mud to prepare water purification filter materials, the problem of waste incineration fly ash and red mud is solved, and the effect of efficient adsorbing heavy metal pollutants is achieved.

CN119819253APending Publication Date: 2025-04-15CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510055358.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

There are shortcomings in the treatment methods for waste incineration fly ash and red mud. The solidification/stabilization technology increases the landfill cost, the safety landfill cost is high and unbearable, and the storage of both will cause land pollution.

Method used

Water purification filter is prepared by collaboratively incineration of fly ash and red mud by waste. Specific steps include mixing red mud and fly ash, calcining waste and incinerating fly ash, mixing sulfur slag, mud ash mixture and calcined ash, filtering and drying through a filter screen after hydrothermal reaction, obtaining efficient water purification filter material.

Benefits of technology

It realizes the conversion of waste into high-efficiency water purification filter and quickly adsorbs heavy metal pollutants. The maximum adsorption capacity of Pb, Hg, and Cr(VI) is greater than 220mg/g, solving the problems of waste disposal and water pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819253A_ABST
    Figure CN119819253A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a water purification filter material by synergistically utilizing waste incineration fly ash and red mud and application of the water purification filter material. The method is simple in preparation process, and the required raw materials are all industrial solid wastes which are wide in source and easy to obtain; the high-efficiency water purification filter material prepared by reasonable proportioning and hydrothermal reaction can quickly adsorb heavy metal pollutants in waste liquid, and the highest adsorption capacities of Pb, Hg and Cr (VI) are all greater than 220mg / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of resource utilization of industrial solid waste, and in particular relates to a method for preparing water purification filter material by collaboratively utilizing waste incineration fly ash and red mud, and application thereof. Background Art

[0002] Waste incineration fly ash is a solid particulate matter produced during the incineration of municipal domestic waste. It is composed of fine particles captured by the flue gas purification system and particles settled at the bottom of the flue and chimney. The particle surface of fly ash is rough, with a large specific surface area and high porosity. The main chemical components of fly ash are CaO, SiO2, Al2O3, Fe2O3, and it contains persistent organic pollutants such as heavy metals and dioxins. Red mud is an insoluble industrial solid waste discharged after the alkaline treatment of bauxite by alumina plants. Its storage will occupy a large amount of land resources and cause land salinization. The high-alkalinity sewage in red mud seeps into the ground or enters surface water, increasing the pH value of the water body, affecting the toxicity of compounds in the water, and causing serious water pollution.

[0003] The main methods for disposing fly ash and red mud from garbage incineration include solidification / stabilization, safe landfill and resource utilization, but these methods all have some shortcomings. Although solidification / stabilization technology can reduce the leaching toxicity of pollutants in fly ash or red mud, the volume of the treated waste increases, increasing the cost and difficulty of subsequent landfill. Under long-term environmental conditions, the solidified body may rupture and pollutants may be released again. The construction and operation costs of safe landfill are extremely high and unbearable.

[0004] The synergistic use of waste incineration fly ash and red mud to prepare water purification filter materials can solve the disposal problems of red mud and waste incineration fly ash at the same time, reduce environmental pollution, and convert waste into valuable water purification filter materials to achieve resource utilization. This research can promote the innovation and development of waste treatment technology and promote scientific and technological progress in related fields. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud and its application.

[0006] Technical solution: The present invention provides a method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud, comprising the following steps:

[0007] (1) mixing red mud and fly ash and stirring evenly to obtain a mud-ash mixture;

[0008] (2) calcining the waste incineration fly ash to obtain calcined ash;

[0009] (3) mixing sulfur slag, mud-ash mixture and calcined ash, stirring evenly, and granulating with a roller to obtain fly ash-based initial filter material;

[0010] (4) placing the fly ash-based initial filter material in a water bath for hydrothermal reaction, wherein the hydrothermal medium is a phosphate aqueous solution, filtering out solid particles through a filter screen after hydrothermal reaction, and obtaining a purified water filter material after drying.

[0011] Furthermore, the mass ratio of the red mud to the fly ash in step (1) is 40 to 120:100.

[0012] Furthermore, the calcination temperature in step (2) is 750-1150° C., and the calcination time is 0.25-1.25 hours.

[0013] Furthermore, the mass ratio of the sulfur slag, mud-ash mixture and calcined ash in step (3) is 5-25:30-90:100.

[0014] Furthermore, the phosphate aqueous solution described in step (4) includes an aqueous solution of any one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, and sodium hexametaphosphate.

[0015] Furthermore, the concentration of the phosphate aqueous solution in step (4) is 0.25 to 3.75 M.

[0016] Furthermore, the hydrothermal time in step (4) is 0.5 to 4.5 hours, the hydrothermal temperature is 120 to 360° C., and the drying temperature is 50 to 150° C.

[0017] The present invention also provides a water purification filter material prepared according to the method.

[0018] The present invention also provides the use of the water purification filter material in treating water bodies containing heavy metal pollutants.

[0019] Furthermore, the heavy metals include any one or more of lead, mercury or hexavalent chromium.

[0020] Reaction mechanism: The waste incineration fly ash is placed in a rotary kiln for calcination. Under high temperature, calcium carbonate, basic calcium chloride and calcium chloride in the waste incineration fly ash decompose to form calcium oxide and release carbon dioxide, hydrogen chloride and chlorine free radicals. Hydrogen chloride and chlorine free radicals can not only further combine with some iron and heavy metal pollutants to form volatile chloride gas, but also catalyze and enhance the thermal decomposition and mineralization reaction of dioxins. Under high temperature, a small amount of gypsum in the waste incineration fly ash is dehydrated to form anhydrous gypsum. Mix the sulfur slag, mud-ash mixture and calcined ash. During the stirring process, the three materials react initially. The acidic substances in the sulfur slag react with the alkaline substances in the red mud to undergo hydrolysis and neutralization. At the same time, the sulfur and sulfide in the sulfur slag react with the trivalent iron and gibbsite in the red mud, the aluminosilicate in the fly ash and the sodium chloride, potassium chloride, anhydrous gypsum and calcium oxide in the calcined ash to form a complex sulfur-iron-calcium gelled mixture of pyroxene, goethite, yellow potassium (sodium) iron alum, iron sulfide, calcium sulfonite and geopolymer. The fly ash-based initial filter material is placed in a water bath for hydrothermal reaction. During the hydrothermal process, the hydration reaction and geopolymer reaction of the fly ash-based initial filter material itself are further deepened. At the same time, the phosphate reacts with the fly ash-based initial filter material to form a phosphorus-calcium-iron-magnesium gelled mixture of calcium phosphate, iron phosphate, tricalcium phosphate, hydroxyapatite, potassium magnesium phosphate hexahydrate, etc. The sulphur-iron-calcium gelled mixture and the phosphate-calcium-iron-magnesium gelled mixture are mixed with each other, and are wrapped by the calcium silicate hydrate colloid and the geopolymer colloid, and harden quickly to form a highly efficient water purification filter material.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the method of the present invention has a simple preparation process, and the required raw materials are all industrial solid waste, which are widely available and easily obtained. The high-efficiency water purification filter material prepared by reasonable ingredients and hydrothermal reaction can quickly adsorb heavy metal pollutants in waste liquid, and the maximum adsorption capacity of Pb, Hg, and Cr (VI) is greater than 220 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0024] Red mud: Red mud was provided by Zibo Zhengheng Aluminum Co., Ltd. The main components tested include: 38.52% Fe2O3, 27.83% Al2O3, 12.49% SiO2, 11.36% Na2O, 5.61% TiO2, 0.57% CaO, 0.34% SO3 and other components (inevitable impurities and ignition loss);

[0025] Fly ash: from Taicang Power Plant of Huaneng Power International Co., Ltd., mainly including 43.21% SiO2, 27.08% Al2O3, 15.62% Fe2O3, 6.58% CaO, 3.42% TiO2, 1.43% SO3, 1.04% K2O, 0.63% Na2O and other components (unavoidable impurities and ignition loss);

[0026] Waste incineration fly ash: Waste incineration fly ash is provided by the Second Municipal Waste Incineration Power Plant in Changshu, Jiangsu Province, mainly including 38.14% CaO, 24.05% Cl, 10.21% SO3, 12.15% Na2O, 6.21% K2O, 3.17% SiO2, 1.41% Fe2O3, 1.19% Al2O3 and other components (loss on ignition and other inevitable impurities);

[0027] Sulfur slag: Sulfur slag comes from the coal gas desulfurization section of the coking plant of Benxi Iron and Steel Group Corporation. Its main chemical components are 10.41% Fe2O3, 21.56% FeO, 0.54% P2O5, 5.28% TiO2, 27.15% SiO2, 24.57% Al2O3, 0.16% MgO, 0.02% MnO, 0.71% CaO, 0.24% Na2O, 0.43% K2O, 6.28% S and other components (loss on ignition and other inevitable impurities).

[0028] Example 1 Effect of the mass ratio of red mud and fly ash on the adsorption performance of the prepared water purification filter material

[0029] Red mud and fly ash are mixed in a mass ratio of 25:100, 30:100, 35:100, 40:100, 80:100, 120:100, 130:100, 140:100, and 150:100, and stirred evenly to obtain a mud-ash mixture. The fly ash from garbage incineration is placed in a rotary kiln for calcination to obtain calcined ash, wherein the calcination temperature is 750°C and the kiln calcination time is 0.25 hours. Sulfur slag, mud-ash mixture, and calcined ash are mixed in a mass ratio of 5:30:100, stirred evenly, and granulated by rollers to obtain fly ash-based initial filter material. Phosphate is dissolved in an aqueous solution to prepare a 0.25M phosphate aqueous solution, wherein the phosphate is sodium phosphate. The fly ash-based initial filter material is placed in a water bath for hydrothermal reaction, solid particles are filtered out through a filter screen after hydrothermal reaction, and purified water filter material is obtained after drying, wherein the hydrothermal medium is a phosphate aqueous solution, the hydrothermal time is 0.5 hours, the hydrothermal temperature is 120°C, and the drying temperature is 50°C.

[0030] Treatment of water containing heavy metal pollutants: According to the solid-liquid ratio of the prepared water purification filter material to the water containing heavy metal pollutants of 1:1 (g / L), the water purification filter material was respectively put into the heavy metal pollutant water containing 500 mg / L lead, 500 mg / L mercury, and 500 mg / L hexavalent chromium, and stirred at 120 rpm for 30 minutes.

[0031] Heavy metal concentration detection and adsorption capacity calculation: Determine the concentration of dissolved mercury in the solution according to the standard "Determination of mercury, arsenic, selenium, bismuth and antimony in water quality by atomic fluorescence method" (HJ695-2014). Determine the concentration of lead in the solution according to the standard "Determination of 32 elements in water quality by inductively coupled plasma emission spectrometry" (HJ776-2015). Determine the concentration of chromium (hexavalent) pollutants in the water body according to the standard "Determination of hexavalent chromium in water quality by diphenylcarbazide spectrophotometry" (GBT7467-1987). The adsorption performance of the water purification filter material is calculated according to formula (1), where q e is the amount of mercury, lead or chromium (hexavalent) adsorbed by the water purification filter material in mg / g, c0 and c t are the concentrations of mercury, lead or chromium (hexavalent) dissolved in the solution before and after the adsorption experiment in mg / L, V is the volume of the solution containing mercury, lead or chromium (hexavalent) in L (1L), and m is the amount of water purification filter material added (1g). The test results are shown in Table 1.

[0032]

[0033] Table 1 Effect of red mud and fly ash mass ratio on adsorption performance of prepared water purification filter media

[0034]

[0035] It can be seen from Table 1 that when the mass ratio of red mud to fly ash is less than 40:100 (such as in Table 1, the mass ratio of red mud to fly ash = 35:100, 30:100, 25:100 and lower ratios not listed in Table 1), less red mud is added, and the sulfur slag, mud-ash mixture and calcined ash react insufficiently, resulting in the prepared water purification filter material. The adsorption capacity of mercury, lead and hexavalent chromium is significantly reduced as the mass ratio of red mud to fly ash decreases. When the mass ratio of red mud to fly ash is equal to 40-120:100 (as in Table 1, the mass ratio of red mud to fly ash = 40:100, 80:100, 120:100), sulfur slag, mud-ash mixture, and calcined ash are mixed. During the stirring process, the three materials react initially, and the acidic substances in the sulfur slag and the alkaline substances in the red mud undergo hydrolysis and neutralization reactions. At the same time, the sulfur and sulfide in the sulfur slag will react with the trivalent iron and gibbsite in the red mud, the aluminosilicate in the fly ash, and the sodium chloride, potassium chloride, anhydrous gypsum, and calcium oxide in the calcined ash to form a complex sulfur-iron-calcium gelled mixture of pyroxene, goethite, yellow potassium (sodium) iron alum, iron sulfide, calcium sulfonite, and geopolymer. Finally, the prepared water purification filter material has a mercury adsorption capacity greater than 189 mg / g, a lead adsorption capacity greater than 215 mg / g, and a hexavalent chromium adsorption capacity greater than 209 mg / g. When the mass ratio of red mud to fly ash is greater than 120:100 (as in Table 1, the mass ratio of red mud to fly ash = 130:100, 140:100, 150:100 and higher ratios not listed in Table 1), excessive red mud is added and the reaction between materials is unbalanced, resulting in a significant decrease in the adsorption capacity of mercury, lead and hexavalent chromium of the water purification filter material as the mass ratio of red mud to fly ash further increases.

[0036] Therefore, in summary, considering benefits and costs, when the mass ratio of red mud to fly ash is equal to 40-120:100, it is most conducive to improving the adsorption performance of the prepared water purification filter material.

[0037] Example 2 Effect of the mass ratio of sulfur slag, mud ash mixture and calcined ash on the adsorption performance of the prepared water purification filter material

[0038] The red mud and fly ash are mixed in a mass ratio of 120:100 and stirred evenly to obtain a mud-ash mixture. The waste incineration fly ash is placed in a rotary kiln for calcination to obtain calcined ash, wherein the calcination temperature is 950° C. and the kiln calcination time is 0.75 hours. Sulphur slag, mud ash mixture and calcined ash are mixed in a mass ratio of 2:30:100, 3:30:100, 4:30:100, 5:15:100, 5:20:100, 5:25:100, 5:30:100, 15:30:100, 25:30:100, 5:60:100, 15:60:100, 25:60:100, 5:90:100, 15:90:100, 25:90:100, 25:100:100, 25:110:100, 25:120:100, 27.5:90:100, 30:90:100 and 32.5:90:100, stirred evenly, and granulated by roller to obtain a fly ash-based initial filter material. Phosphate is dissolved in an aqueous solution to prepare a 2M phosphate aqueous solution, wherein the phosphate is sodium dihydrogen phosphate. The fly ash-based initial filter material is placed in a water bath for hydrothermal reaction, solid particles are filtered out through a filter screen after hydrothermal reaction, and purified water filter material is obtained after drying, wherein the hydrothermal medium is a phosphate aqueous solution, the hydrothermal time is 3 hours, the hydrothermal temperature is 240°C, and the drying temperature is 100°C.

[0039] The treatment of water containing heavy metal pollutants, the detection of heavy metal concentrations and the calculation of adsorption capacity are all the same as in Example 1.

[0040] Table 2 Effect of the mass ratio of sulfur slag, mud ash mixture and calcined ash on the adsorption performance of the prepared water purification filter material

[0041]

[0042]

[0043] It can be seen from Table 2 that when the mass ratio of sulfur slag, mud-lime mixture and calcined ash is less than 5:30:100 (such as in Table 2, the mass ratio of sulfur slag, mud-lime mixture and calcined ash = 4:30:100, 3:30:100, 2:30:100, 5:25:100, 5:20:100, 5:15:100 and lower ratios not listed in Table 2), less sulfur slag and mud-lime mixture are added, and the material reaction is not sufficient, resulting in the prepared water purification filter material The adsorption capacity of mercury, lead and hexavalent chromium is significantly reduced as the mass ratio of sulfur slag, mud-lime mixture and calcined ash decreases. When the mass ratio of sulfur slag, mud ash mixture and calcined ash is 5-25:30-90:100 (as in Table 2, the mass ratio of sulfur slag, mud ash mixture and calcined ash = 5:30:100, 15:30:100, 25:30:100, 5:60:100, 15:60:100, 25:60:100, 5:90:100, 15:90:100, 25:90:100), the sulfur slag, mud ash mixture and calcined ash are mixed. The mixture and calcined ash react initially during the stirring process. The acidic substances in the sulfur slag react with the alkaline substances in the red mud to undergo hydrolysis and neutralization. At the same time, the sulfur and sulfide in the sulfur slag react with the trivalent iron and gibbsite in the red mud, the aluminosilicate in the fly ash, and the sodium chloride, potassium chloride, anhydrous gypsum, and calcium oxide in the calcined ash to form a complex sulfur-iron-calcium gelled mixture of pyroxene, goethite, yellow potassium (sodium) iron alum, iron sulfide, calcium sulfonite, and geopolymer. Finally, the prepared water purification filter material has a mercury adsorption capacity greater than 209 mg / g, a lead adsorption capacity greater than 238 mg / g, and a hexavalent chromium adsorption capacity greater than 229 mg / g. When the mass ratio of sulfur slag, mud-lime mixture and calcined ash is greater than 25:90:100 (as in Table 2, the mass ratio of sulfur slag, mud-lime mixture and calcined ash = 25:100:100, 25:110:100, 25:120:100, 27.5:90:100, 30:90:100, 32.5:90:100 and higher ratios not listed in Table 2), excessive addition of sulfur slag and mud-lime mixture causes an imbalance in the reaction between the materials, resulting in a significant decrease in the adsorption capacity of mercury, lead and hexavalent chromium for the water purification filter material as the mass ratio of sulfur slag, mud-lime mixture and calcined ash further increases.

[0044] Therefore, in summary, considering the benefits and costs, when the mass ratio of sulfur slag, mud ash mixture and calcined ash is equal to 5-25:30-90:100, it is most conducive to improving the adsorption performance of the prepared water purification filter material.

[0045] Example 3 Effect of hydrothermal time on adsorption performance of prepared water purification filter material

[0046] Red mud and fly ash are mixed in a mass ratio of 120:100, stirred evenly, and a mud-ash mixture is obtained. The fly ash from garbage incineration is placed in a rotary kiln for calcination to obtain calcined ash, wherein the calcination temperature is 1150°C and the kiln calcination time is 1.25 hours. Sulfur slag, mud-ash mixture, and calcined ash are mixed in a mass ratio of 25:90:100, stirred evenly, and granulated by roller to obtain fly ash-based initial filter material. Phosphate is dissolved in an aqueous solution to prepare a 3.75M phosphate aqueous solution, wherein the phosphate is disodium hydrogen phosphate. The fly ash-based initial filter material is placed in a water bath for hydrothermal reaction, the solid particles are filtered out through a filter screen after hydrothermal reaction, and the purified water filter material is obtained after drying, wherein the hydrothermal medium is a phosphate aqueous solution, the hydrothermal time is 0.2 hour, 0.3 hour, 0.4 hour, 0.5 hour, 2.5 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours, the hydrothermal temperature is 360°C, and the drying temperature is 150°C.

[0047] The treatment of water containing heavy metal pollutants, the detection of heavy metal concentrations and the calculation of adsorption capacity are all the same as in Example 1.

[0048] Table 3 Effect of hydrothermal time on adsorption performance of prepared water purification filter media

[0049]

[0050]

[0051] It can be seen from Table 3 that when the hydrothermal time is less than 5:30:100 (such as in Table 3, when the hydrothermal time = 0.4 hours, 0.3 hours, 0.2 hours and lower values ​​not listed in Table 3), the hydrothermal time is short, the material reaction is insufficient, resulting in the prepared water purification filter material mercury, lead, hexavalent chromium adsorption capacity are significantly reduced as the hydrothermal time decreases. When the hydrothermal time is equal to 0.5 to 4.5 hours (such as in Table 3, the hydrothermal time = 0.5 hours, 2.5 hours, 4.5 hours), the fly ash-based initial filter material is placed in a water bath for hydrothermal reaction. During the hydrothermal process, the hydration reaction and geopolymer reaction of the fly ash-based initial filter material itself are further deepened, and at the same time, phosphate reacts with the fly ash-based initial filter material to generate a phosphate calcium iron magnesium gelled mixture mixed with calcium phosphate, iron phosphate, tricalcium phosphate, hydroxyapatite, potassium magnesium phosphate hexahydrate, etc. The sulfur-iron calcium gelled mixture and the phosphorus-calcium-iron-magnesium gelled mixture are intermixed and mixed with each other, and are wrapped by the calcium silicate hydrate colloid and the geopolymer colloid, and harden quickly to form a highly efficient water purification filter material. Finally, the prepared water purification filter material has a mercury adsorption capacity greater than 230 mg / g, a lead adsorption capacity greater than 257 mg / g, and a hexavalent chromium adsorption capacity greater than 249 mg / g. When the hydrothermal time is greater than 4.5 hours (as in Table 3, the hydrothermal time = 5 hours, 5.5 hours, 6 hours, and higher values ​​not listed in Table 3), the hydrothermal time is too long, and the reaction between the materials is unbalanced, resulting in the water purification filter material mercury, lead, and hexavalent chromium adsorption capacity are significantly reduced as the hydrothermal time further increases.

[0052] Therefore, in summary, considering the benefits and costs, when the hydrothermal time is equal to 0.5 to 4.5 hours, it is most conducive to improving the adsorption performance of the prepared water purification filter material.

[0053] Example 4 Effect of Phosphate Type on the Adsorption Performance of Prepared Water Purification Filter Material

[0054] Red mud and fly ash are mixed in a mass ratio of 120:100, stirred evenly, and a mud-ash mixture is obtained. The fly ash from garbage incineration is placed in a rotary kiln for calcination to obtain calcined ash, wherein the calcination temperature is 1150°C and the kiln calcination time is 1.25 hours. Sulfur slag, mud-ash mixture, and calcined ash are mixed in a mass ratio of 25:90:100, stirred evenly, and granulated by rollers to obtain fly ash-based initial filter material. Phosphate is dissolved in an aqueous solution to prepare a 3.75M phosphate aqueous solution, wherein the phosphate is any one of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, and sodium hexametaphosphate. The fly ash-based initial filter material is placed in a water bath for hydrothermal reaction, and the solid particles are filtered out through a filter screen after hydrothermal reaction, and a clean water filter material is obtained after drying, wherein the hydrothermal medium is a phosphate aqueous solution, the hydrothermal time is 4.5 hours, the hydrothermal temperature is 360°C, and the drying temperature is 150°C.

[0055] The treatment of water containing heavy metal pollutants, the detection of heavy metal concentrations and the calculation of adsorption capacity are all the same as in Example 1.

[0056] Table 4 Effect of phosphate type on adsorption performance of prepared water purification filter media

[0057]

[0058] It can be seen from Table 4 that when the phosphate is any one of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, and sodium hexametaphosphate, there is no significant difference in the adsorption performance of the prepared water purification filter material.

[0059] Comparative example: Effects of different comparative processes on the adsorption performance of prepared water purification filter media

[0060] The process of the present invention is as follows: red mud and fly ash are mixed in a mass ratio of 120:100, stirred evenly, and a mud-ash mixture is obtained. The fly ash from garbage incineration is placed in a rotary kiln for calcination to obtain calcined ash, wherein the calcination temperature is 1150°C and the kiln calcination time is 1.25 hours. Sulfur slag, mud-ash mixture, and calcined ash are mixed in a mass ratio of 25:90:100, stirred evenly, and granulated by rollers to obtain fly ash-based initial filter material. Phosphate is dissolved in an aqueous solution to prepare a 3.75M phosphate aqueous solution, wherein the phosphate is sodium hexametaphosphate. The fly ash-based initial filter material is placed in a water bath for hydrothermal reaction, and solid particles are filtered out through a filter screen after hydrothermal reaction, and purified water filter material is obtained after drying, wherein the hydrothermal medium is a phosphate aqueous solution, the hydrothermal time is 4.5 hours, the hydrothermal temperature is 360°C, and the drying temperature is 150°C.

[0061] Comparative process 1: Place the fly ash from garbage incineration in a rotary kiln for calcination to obtain calcined ash, wherein the calcination temperature is 1150°C and the kiln calcination time is 1.25 hours. Mix sulfur slag, red mud and calcined ash in a mass ratio of 25:90:100, stir evenly, and granulate with a roller to obtain fly ash-based initial filter material. Dissolve phosphate in an aqueous solution to prepare a 3.75M phosphate aqueous solution, wherein the phosphate is sodium hexametaphosphate. Place the fly ash-based initial filter material in a water bath for hydrothermal reaction, filter out solid particles through a filter screen after hydrothermal reaction, and obtain a clean water filter material after drying, wherein the hydrothermal medium is a phosphate aqueous solution, the hydrothermal time is 4.5 hours, the hydrothermal temperature is 360°C, and the drying temperature is 150°C.

[0062] Comparative process 2: Red mud and fly ash are mixed in a mass ratio of 120:100, stirred evenly, and a mud-ash mixture is obtained. The fly ash from garbage incineration is placed in a rotary kiln for calcination to obtain calcined ash, wherein the calcination temperature is 1150°C and the kiln calcination time is 1.25 hours. The mud-ash mixture and calcined ash are mixed in a mass ratio of 90:100, stirred evenly, and granulated by rollers to obtain fly ash-based initial filter material. Phosphate is dissolved in an aqueous solution to prepare a 3.75M phosphate aqueous solution, wherein the phosphate is sodium hexametaphosphate. The fly ash-based initial filter material is placed in a water bath for hydrothermal reaction, and the solid particles are filtered out through a filter screen after hydrothermal reaction, and a clean water filter material is obtained after drying, wherein the hydrothermal medium is a phosphate aqueous solution, the hydrothermal time is 4.5 hours, the hydrothermal temperature is 360°C, and the drying temperature is 150°C.

[0063] The treatment of water containing heavy metal pollutants, the detection of heavy metal concentrations and the calculation of adsorption capacity are all the same as in Example 1.

[0064] Table 5 Effect of different comparative processes on the adsorption performance of prepared water purification filter media

[0065]

[0066] It can be seen from Table 5 that the adsorption performance of the water purification filter material prepared by the process of the present invention is significantly better than that of the water purification filter material prepared by comparative process 1 and comparative process 2.

Claims

1. A method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud, characterized in that: The following steps are involved: (1) mixing red mud and fly ash and stirring evenly to obtain a mud-ash mixture; (2) calcining the waste incineration fly ash to obtain calcined ash; (3) mixing sulfur slag, mud-ash mixture and calcined ash, stirring evenly, and granulating with a roller to obtain fly ash-based initial filter material; (4) placing the fly ash-based initial filter material in a water bath for hydrothermal reaction, wherein the hydrothermal medium is a phosphate aqueous solution, filtering out solid particles through a filter screen after hydrothermal reaction, and obtaining a purified water filter material after drying.

2. The method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud according to claim 1, characterized in that: The mass ratio of red mud to fly ash in step (1) is 40 to 120:

100.

3. The method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud according to claim 1, characterized in that: The calcination temperature in step (2) is 750-1150° C., and the calcination time is 0.25-1.25 hours.

4. The method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud according to claim 1, characterized in that: The mass ratio of the sulfur slag, the mud-ash mixture and the calcined ash in step (3) is 5-25:30-90:

100.

5. The method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud according to claim 1, characterized in that: The phosphate aqueous solution described in step (4) includes any one or more aqueous solutions of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, and sodium hexametaphosphate.

6. The method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud according to claim 1, characterized in that: The concentration of the phosphate aqueous solution described in step (4) is 0.25-3.75M.

7. The method for preparing water purification filter material by synergistically utilizing waste incineration fly ash and red mud according to claim 1, characterized in that: The hydrothermal time in step (4) is 0.5 to 4.5 hours, the hydrothermal temperature is 120 to 360° C., and the drying temperature is 50 to 150° C.

8. A water purification filter material prepared according to any one of claims 1 to 7.

9. Use of the water purification filter material according to claim 8 in treating water bodies containing heavy metal pollutants.

10. The use according to claim 9, characterized in that: The heavy metals include any one or more of lead, mercury or hexavalent chromium.